Silicon oxycarbonitride ceramic containing nickel nanoparticles: from design to catalytic application. Issue 5 (15th February 2021) - Wang, Jun; Gili, Albert; Grünbacher, Matthias; Praetz, Sebastian; Epping, Jan Dirk; Görke, Oliver; Schuck, Götz; Penner, Simon; Schlesiger, Christopher; Schomäcker, Reinhard; Gurlo, Aleksander; Bekheet, Maged F.
Abstract : We report the synthesis of Ni/SiOCN ceramic nanocomposites with high surface area as catalysts for carbon dioxide and methane conversion. Abstract : Nickel-containing silicon oxycarbonitride ceramic nanocomposites are synthesized from hydrous nickel acetate and poly(vinyl)silazane (Durazane 1800) or perhydropolysilazane NN120-20 (A) (PHPS). A room temperature chemical reaction results in Ni-containing polysilazane precursors which are transformed into ceramic nanocomposites with nickel nanoparticles (2–4 nm) upon pyrolysis at elevated temperatures (700–1100 °C) under an argon atmosphere. The ceramic nanocomposites derived from the Durazane 1800-Ni precursor by the thermolysis process at 700 and 900 °C manifest a microporous structure with a BET specific surface area of ∼361 and ∼232 m 2 g −1, respectively. In contrast, all pyrolyzed samples derived from the PHPS-Ni precursor exhibit a nonporous structure. The Ni/SiOCN ceramic nanocomposites – tested in a plug-flow fixed-bed reactor – display significant catalytic activity in dry methane reforming to syngas. The highest CH4 reaction rate of 0.18 mol min −1 gNi −1 is observed at 800 °C for the sample derived from the PHPS-Ni precursor by pyrolysis at 900 °C. All these make the materials developed in this work, i.e. nickel nanoparticles in situ formed in the SiOCN ceramic matrix, as promising candidates for heterogeneous catalysis.